Encyclopedia of Life Sciences 2017
DOI: 10.1002/9780470015902.a0023983
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Genome Size

Abstract: The size of the genome represents one of the most strikingly variable yet poorly understood traits in eukaryotic organisms. Genomic comparisons suggest that most properties of genomes tend to increase with genome size, but the fraction of the genome that comprises transposable elements (TEs) and other repetitive elements tends to increase disproportionately. Neutral, nearly neutral and adaptive models for the evolution of genome size have been proposed, but strong evidence for the general importance of any of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Using phylogenetic generalized linear models, we found that parasitic or pathogenic species had a higher recombination rate compared to their free-living counterparts in SAR and in animals, but there was no difference between parasitic or pathogenic and free-living species of fungi (electronic supplementary material, figure S5; plants were excluded as data were not available for any parasitic or pathogenic plant species). Interestingly, parasites often have smaller genomes compared to their free-living counterparts, which is consistent with high recombination driving genome contraction (discussed earlier in box 2 ), although genome contraction may also be due to selection on small cell size and fast replication rates [ 55 , 169 ].…”
Section: Evolutionary Processes Governing Variation In Recombination mentioning
confidence: 78%
“…Using phylogenetic generalized linear models, we found that parasitic or pathogenic species had a higher recombination rate compared to their free-living counterparts in SAR and in animals, but there was no difference between parasitic or pathogenic and free-living species of fungi (electronic supplementary material, figure S5; plants were excluded as data were not available for any parasitic or pathogenic plant species). Interestingly, parasites often have smaller genomes compared to their free-living counterparts, which is consistent with high recombination driving genome contraction (discussed earlier in box 2 ), although genome contraction may also be due to selection on small cell size and fast replication rates [ 55 , 169 ].…”
Section: Evolutionary Processes Governing Variation In Recombination mentioning
confidence: 78%
“…The relationship between genome size and chromosome number in angiosperms and teleost fish is likely due to these polyploidy events (Hinegardner and Rosen 1972; Pandit et al 2014). The events following these polyploidization events typically result in duplicate gene losses and chromosomal rearrangements which may make these events difficult to identify, and may remove any signal of a relationship between genome and chromosome number (Reviewed in Wright 2017). Chromosome number can also change by fusions or fissions of existing chromosomes, changing chromosome number but not the actual number of chromosome arms (fundamental number) or genic content of the genome (Blackmon et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Genome size varies widely across the tree of life, with no clear correlation to organismal complexity (Mirskey and Ris 1951; Gregory 2001; Palazzo and Gregory 2014). This extreme variation is therefore not attributed to coding sequences in eukaryotes, but rather to differences in non-coding regions such as introns, and inflation of the genome via TEs and repetitive DNA (Gregory and Hebert 1999; Kidwell 2002; Kelley et al 2014; Sessegolo et al 2016; Wright 2017). Among closely related species of plants and closely related Drosophila species, much of the variation in genome size has been explained by the differential accumulation of transposable elements (Bennetzen and Kellogg 1997; Ågren and Wright 2011; Śliwińska et al 2016).…”
mentioning
confidence: 99%
“…Although current genome size estimations place Diptera among the smallest genome sizes in insects, it is not clear how these minimum genome size estimations extend to the rest of insects. Fluctuations in noncoding regions, such as repeat content and transposable elements, drive genome size change (Gregory and Hebert 1999;Kidwell 2002;Sessegolo et al 2016;Wright 2017). Although the relationship between genome size and these noncoding regions is clear, the patterns by which these late-replicating heterochromatic regions and early-replicating, mostly euchromatic regions evolve are largely unknown.…”
Section: Subgeneramentioning
confidence: 99%